2023
DOI: 10.1039/d2sc06986e
|View full text |Cite
|
Sign up to set email alerts
|

Real-time monitoring of the sialic acid biosynthesis pathway by NMR

Abstract: Sialic acids are part of the outermost component of the glycocalyx of all vertebrates; as such, they are fundamental markers in physiological and pathological processes. In this study, we introduce...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 55 publications
0
4
1
Order By: Relevance
“…While a recent study implies, that exogenous ManNAc is phosphorylated by NAGK ( Gorenflos Lopez et al. 2023 ), our results show that even with Nagk being expressed in C2C12 Gne-KO cells, there is no ManNAc phosphorylation.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…While a recent study implies, that exogenous ManNAc is phosphorylated by NAGK ( Gorenflos Lopez et al. 2023 ), our results show that even with Nagk being expressed in C2C12 Gne-KO cells, there is no ManNAc phosphorylation.…”
Section: Discussioncontrasting
confidence: 93%
“…It has been shown that the N-acetylglucosmaine kinase (NAGK) is able to phosphorylate ManNAc, and is thus believed to bypass the lack of GNE kinase activity in GNE-deficient cells ( Allen and Walker 1980 ). A recent study also suggests that external ManNAc is mainly phosphorylated by NAGK ( Gorenflos Lopez et al. 2023 ).…”
Section: Resultsmentioning
confidence: 93%
“…With wt-NAGK, pS76-NAGK, and ppS76-NAGK in hand, we next wanted to evaluate how the different phosphorylation modes influenced the enzymatic activity of NAGK. To do so, a standard kinase assay was set up using GlcNAc as a substrate and monitoring adenosine-5′-triphosphate (ATP) consumption (Figure a) . At low enzyme concentration (1 nM), unphosphorylated wt-NAGK displayed a robust activity of 260 nmol/min/ng.…”
Section: Resultsmentioning
confidence: 99%
“…To do so, a standard kinase assay was set up using GlcNAc as a substrate and monitoring adenosine-5′triphosphate (ATP) consumption (Figure 3a). 28 At low enzyme concentration (1 nM), unphosphorylated wt-NAGK displayed a robust activity of 260 nmol/min/ng. By contrast, pSer76-NAGK showed no activity at 1 nM enzyme concentration.…”
Section: Synthesis Of Pyrophosphorylated Nagkmentioning
confidence: 95%
“…The primary hits were validated with a plate reader‐independent and orthogonal NMR‐assay [18] . The N ‐acetyl methyl of UDP‐GlcNAc and ManNAc were found to display characteristic chemical shifts around 2.1–1.9 ppm (Supplementary Figure 12).…”
Section: Resultsmentioning
confidence: 99%